Tuning the phase diagrams: the miscibility studies of multilactate liquid crystalline compounds. (1st September 2016) - Bubnov, Alexej; Tykarska, Marzena; Hamplová, Věra; Kurp, Katarzyna
Abstract : Design of binary and multicomponent liquid crystalline mixtures is a very powerful tool to reach the desired self-assembling properties. Beyond many advantages, this method has a distinct negativity – it is very material-consuming. While working with unique chiral materials in the research laboratory, this problem can be solved by applying miscibility study by the contact preparation method. In this work, the miscibility studies of lactic acid derivatives and non-chiral/chiral liquid crystalline molecules of different structure have been done in order to establish the phase diagrams. Special attention is focused on the ferro(antiferro)electric smectic phases.